Optimization of Business Opportunities as Predictor of Growth of Metal Fabrication Microenterprises in Kisii County: The Moderating Role of Owner’s Level of Education - Orina, Kennedy Omwenga (JOOUST, 2024)
Reports by The Kenya National Bureau of Statistics indicate that despite the metal fabrication sector making 12% of the small manufacturers in Kenya and contributing 10% to GDP the sector face growth challenges leading to over 70% failure within the first three years. This study sought to analyse the optimization of business opportunities for growth of metal fabrication MEs in Kisii County as moderated by owner level of education. Specifically, this study sought to examine the influence of business opportunities in finance, marketing, technology and government regulatory framework in the growth of metal fabrication MEs. This study is anchored in Senge’s Learning Organization model which states that organizations can recognize and take advantage of opportunities in their business environment for competitiveness and growth. This is supported by Enterprise Life-cycle model, Porter’s Generic Strategies and SWOT Analysis. Guided by positivistic approach together with a longitudinal survey, a mixed design involving quantitative and qualitative designs was used to obtain information from 255 Metal fabrication MEs in Kisii County. Purposive stratified sampling was used to classify these firms into five subsectors: wielding, motor vehicle panel beating, auto and industrial spare parts, key cutting and padlocks, and blacksmith adding to 155 metal fabrication MEs in Kisii, Ogembo and Suneka towns. A self-administered questionnaire and interview were used to collect data from 115 respondents who were the metal fabrication MEs owners/ managers and chairman of the Jua Kali Sacco respectively. A pilot study was done in Nyamache Town in Kisii County. Reliability and validity tests were done to ensure that the instruments were appropriate and measured the required data. Data was analyzed using SPSS and descriptive statistics such mean scores, variances, standard deviation and inferential statistics namely; correlation and regression were used to present and analyse the data. Bivariate correlations and regression results were also used to test the hypotheses. Moderated regression analysis was used to establish the moderating effect of owner level of education on the relationship between optimization of business opportunities and the growth of the MEs. The results showed that optimization of business opportunities is a significant predictor of the growth of the metal fabrication MEs. The findings also showed that owner level of education is a significant moderator of the relationship between optimization of business opportunities and growth of metal fabrication MEs. Specifically, all the four business opportunities (financial, technology, marketing and government regulatory policies) tested in this study were found to be significant and of positive influence on the growth of metal fabrication MEs. The study also noted that age, level of education and experience of owner/ managers of the MEs significantly influenced the relationship between optimization of business opportunities and growth of metal fabrication MEs. In the practice, this study recommends that MEs invest in information technology for updated information and developments in their trade, build a strong asset portfolio to meet the collateral requirements, register their businesses to improve their credit worthiness, partner through SACCOs to enhance bargaining power, exchange and bench marking ideas and knowledge for technological and innovation excellence, and spur horizontal integration for growth. On methodology, the study recommends further studies featuring multiple moderating variables and growth of metal fabrication MEs in other counties. On policy, the study recommends that the Kenyan government develop a policy framework that focuses on financial, technological needs and improvements; market and capacity building to enable the metal fabrication MEs grow and transit from informal to formal enterprises.
Keywords: Metal Fabrication Microenterprises